BIOMASS AND NUTRIENT CYCLING BY COVER CROPS IN BRAZILIAN CERRADO IN THE STATE OF PIAUI - Pacheco, Leandro Pereira (2016)
Research on the performance of cover crops in crop systems of annual crops in the Brazilian state of Piauí contributes to increases in yield, greater efficiency of fertilizers and mitigation of environmental impacts. The aim of this study was to evaluate the performance of cover crops in terms of biomass production and the accumulation and release of nutrients during the crop season (November to April) in an oxisol in the Brazilian Cerrado in the state of Piauí that was submitted to different crop production systems including soybeans, maize and upland rice. The experiment was established during the 2010/11 and 2011/12 crop years in the rural area near the municipality of Bom Jesus, Piauí. The experimental design was a randomized block in a split-plot array. Different soil management systems (conventional and no-till) were evaluated in the main plots. Different crop production systems consisting of cover crops sown in the off-season (April to November), and annual crops sown during the crop season (November to April) were implemented in the subplots. The crop production systems that included Urochloa ruziziensis and Pennisetum glaucum overseeded on soybeans and Urochloa ruziziensis simultaneously intercropped with maize stood out in terms of biomass production and the accumulation and release of nutrients. Yields of maize and upland rice declined when sown under newly implemented no-till soil management.